Cost-effectiveness of contrast-enhanced breast MRI in suspicious mammographic microcalcifications - Barbara J. Fueger; Fabian Tollens; Clemens G. N. Kaiser; Thomas H. Helbich; Nina Pötsch; Paola Clauser; Pascal A. T. Baltzer (Insights into Imaging)
Abstract Objectives To evaluate the cost-effectiveness of supplemental breast magnetic resonance imaging (MRI) in women with BI-RADS 4 mammographic microcalcifications in order to avoid unnecessary stereotactic biopsies. Methods Decision analysis and Markov modeling were used to compare the short-term costs and effects of two diagnostic strategies: supplemental breast MRI in women with mammographic microcalcifications to avoid needle biopsies in MRI negative cases vs stereotactic biopsies of all BI-RADS 4 microcalcifications. Results Applying supplemental breast MRI resulted in comparable costs and outcomes. Average cumulative costs of US$ 56,918 and 2.932 quality adjusted life years (QALYs) per woman were achieved for the supplemental breast MRI-strategy, whereas stereotactic biopsies as standard of care resulted in cumulative costs of US$ 56,898 and 2.930 QALYs, resulting in an incremental cost effectiveness ratio (ICER) of US$ 10,047 per QALY gained. Conclusion Due to comparable diagnostic safety at similar costs, the non-invasive breast MRI alternative for workup of mammographically detected suspicious calcifications should be offered to patients within the context of shared decision making. Critical relevance statement Contrast-enhanced MRI of the breast should be offered as an alternative to stereotactic biopsy within the context of shared decision-making. Key Points Breast MRI and stereotactic biopsy enable accurate risk stratification of suspicious calcifications. Breast MRI and stereotactic biopsy yield comparable cost-effectiveness and clinical outcomes. Breast MRI should be considered as an option regarding shared clinical decision-making. Graphical Abstract